2017
DOI: 10.18632/oncotarget.15665
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of failure and clinical outcomes of definitive radiotherapy for cervical esophageal cancer

Abstract: PurposeBecause of the scarcity of cervical esophageal cancer (CEC), data for this disease entity is limited. We aim to evaluate the outcomes, prognostic factors and failure patterns of CEC treated by contemporary radiotherapy (RT).MethodsWe retrospectively analyzed 86 CEC patients consecutively treated between 2007 and 2015 by definitive RT with or without concurrent chemotherapy. RT was mainly delivered with Intensity Modulated Irradiation Therapy (IMRT) or Volumetric-Modulated Arc Therapy (VMAT). Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…19 However, a study by Gkika et al (n = 55, CEC treated with CCRT) also suggested that a higher radiation dose (>60 Gy vs ≤60Gy) did not lead to better 5-year OS (24% vs 26%, p = 0.78). 16 In our previous study 27 including 97 patients with CEC who received doses of 95% PGTV 50-70 Gy (median 66 Gy) and 95% PTV 40-60 Gy (median 55 Gy) because of adverse reactions, we also arrived at the same conclusion as Cao et al 19 , that a higher 95% PGTV dose (≥66 Gy) improved the OS. While, in our current study, when the completed doses for 95% PGTV and 95% PTV were raised to 59.4-70 Gy (median 66 Gy) and 50-60 Gy (median 58 Gy) respectively, we could not confirm the beneficial effects of higher dose radiation (shown in Appendix Figure 1).…”
Section: Discussionsupporting
confidence: 70%
“…19 However, a study by Gkika et al (n = 55, CEC treated with CCRT) also suggested that a higher radiation dose (>60 Gy vs ≤60Gy) did not lead to better 5-year OS (24% vs 26%, p = 0.78). 16 In our previous study 27 including 97 patients with CEC who received doses of 95% PGTV 50-70 Gy (median 66 Gy) and 95% PTV 40-60 Gy (median 55 Gy) because of adverse reactions, we also arrived at the same conclusion as Cao et al 19 , that a higher 95% PGTV dose (≥66 Gy) improved the OS. While, in our current study, when the completed doses for 95% PGTV and 95% PTV were raised to 59.4-70 Gy (median 66 Gy) and 50-60 Gy (median 58 Gy) respectively, we could not confirm the beneficial effects of higher dose radiation (shown in Appendix Figure 1).…”
Section: Discussionsupporting
confidence: 70%
“…The most common failure pattern of concurrent chemoradiotherapy is local failure . Recurrences in the target region are extremely rare, and reduction of the incidence is largely dependent on adequate irradiation, which indicates to us that the greatest challenge of esophageal cancer radiotherapy is achieving an adequate dose to the gross tumor volume while minimizing toxicity to the surrounding critical normal tissues …”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the 5-year survival rates of CESCC were reported to be 18–35% ( 8 , 23 , 24 ). These results are similar to those for thoracic esophageal cancer ( 3 5 ).…”
Section: Introductionmentioning
confidence: 97%